2008
DOI: 10.3151/jact.6.443
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shear Crack Width in I-Shaped Prestressed Reinforced Concrete Beams

Abstract: Recently, Prestressed Reinforced Concrete (PRC) has been accepted as a reasonable structural member that permits cracking. A PRC member is a visible design alternative to either reinforced concrete (RC) or fully prestressed concrete (PC). In Japan, PRC has been widely used for bridge structures because it is economical. PRC members are generally designed to allow cracking under full service loads. Flexural cracking in PRC beams has been already studied and the flexural crack width can be accurately predicated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
25
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 4 publications
4
25
0
Order By: Relevance
“…Except for two specimens, all experimental results are overestimated with the average experi- mental-to-predicted shear crack spacing ratio of 0.75. The two underestimated predictions are for specimens IRC-2 10) and B 3 right shear span 1) , in both of which the side concrete cover to shear reinforcement (c s ) is relatively great (69 and 80 mm, respectively). The reason of the two underestimated predictions is the fact that Collins and Mitchell model does not take into account for the effect of the side concrete cover to shear reinforcement on shear crack spacing.…”
Section: ) Evaluation Of the Existing Shear Crack Spacing Predictionmentioning
confidence: 99%
See 3 more Smart Citations
“…Except for two specimens, all experimental results are overestimated with the average experi- mental-to-predicted shear crack spacing ratio of 0.75. The two underestimated predictions are for specimens IRC-2 10) and B 3 right shear span 1) , in both of which the side concrete cover to shear reinforcement (c s ) is relatively great (69 and 80 mm, respectively). The reason of the two underestimated predictions is the fact that Collins and Mitchell model does not take into account for the effect of the side concrete cover to shear reinforcement on shear crack spacing.…”
Section: ) Evaluation Of the Existing Shear Crack Spacing Predictionmentioning
confidence: 99%
“…Due to the limited space, full details of the geometric and material properties of these specimens could not be shown in this paper. The collected data covers a wide range of parameters and studied values as following: 1) All the investigated specimens are RC and PC beams with vertical shear reinforcements; 2) those specimens were tested under static loading except specimens tested under fatigue loading by Hassan 11) ; 3) those specimens experienced shear failure; 4) those specimens are rectangular beams except specimens tested by De Silva et al 10) which are I-shaped beams; 5) the shear reinforcing bars are deformed reinforcing bar in all the specimens except specimens VPS10 right, VPS10 left, VPS13 right and VPS13 left tested by Hassan 11) , and specimen IPRC-3 examined by De Silva et al 10) in which plain shear reinforcing bars were used; 6) the shear reinforcement configuration is closed form in all the specimens except one shear span of a specimen (specimen B 1 ) tested by Zakaria et al 1) where open (special) stirrup configuration was applied; 7) the range of various parameters are 270 mm to 750 mm for overall height, 150 mm to 300 mm for web width, 224.12 mm to 669.00 mm for effective depth based on total longitudinal steel including prestressing tendon, 2.00 to 4.00 for shear span-to-effective depth ratio, 1.62% to 6.44% for longitudinal reinforcement ratio including prestressing tendon, 0.11% to 1.00% for shear reinforcement ratio, 20.0 mm to 80.0 mm for side concrete cover to shear reinforcement, 39.6 mm to 410.0 mm for shear reinforcement spacing, and 0.0 MPa to 5.0 MPa for prestress level; 8) Specimens IRC-1 and IRC-2 tested by De Silva et al 10) as well as specimen S-2 tested by Witchukreangkrai et al 8) were not considered in the analysis for shear crack width due to the unreasonable nature of the measured data as discussed in section 5. (2).…”
Section: Description Of Investigated Specimens and Collected Test Resmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, prestressed reinforced concrete (PRC) has been accepted as a reasonable structural member that permits cracking. On the basis of the experiment program including the influence of prestressing force, side concrete cover, stirrup spacing, bond characteristics of stirrup and the amount of longitudinal reinforcement on shear crack width, the research (Silva et al 2008) revealed that the prestressing force significantly reduced shear crack width in PRC beams as compared to RC beams.…”
Section: Crack-controlled Design Formulas For Rc Beam and Column Membersmentioning
confidence: 99%